Silica Particles Mediate Phenotypic and Functional Alteration of Dendritic Cells and Induce Th2 Cell Polarization - Liu, Suna; Hao, Changfu; Bao, Lei; Zhao, Dehua; Zhang, Hongyi; Hou, Jianyong; Wang, Di; Chen, Huiting; Feng, Feifei; Yao, Wu (Frontiers in Immunology, 2019)
During silicosis, immune cells, including macrophages, T cells, B cells, and NK cells, participate in fibrosis development through alteration of the immune status. Dendritic cells (DCs) are professional antigen-presenting cells (APCs) with a key role in initiating immune responses and sustaining immune tolerance to maintain homeostasis. The relative contribution of DCs to silicosis progression is not well-documented. In the current study, we investigated the phenotypic and functional alterations of peripheral blood mononuclear cell (PBMC)-derived DCs of Sprague–Dawley (SD) rat during immune responses to silica exposure. We established models for direct and indirect exposure of DCs to silica by either treating DCs with silica or coculturing them with alveolar macrophages (AMs) treated with silica, respectively. The functional activity of DCs was analyzed by measuring their expression of costimulatory molecules, fluorescent microparticle uptake, cytokine production, and ability to mediate T cell polarization in vitro. In vivo, we demonstrated that silica could induce DC migration in response to silica exposure. Our results show that cytokine production by DCs was increased in response to direct silica direct exposure, while indirect silica exposure led to reduced cytokine levels. Moreover, the phagocytic capacity of DCs increased in cocultures after silica exposure. Gene and protein expression analyses showed that silica exposure altered the expression levels of Toll-like receptor pathway proteins and inflammatory factors. DC surface expression of the costimulatory molecules, CD80, CD86, and major histocompatibility complex, was inhibited by exposure to silica, which mediated a Th2-polarizing response in vitro. In rats, silica exposure induced migration of DCs from the peripheral blood into the alveoli. These results demonstrate that direct and indirect exposure to silica particles alter the phenotype and function of DCs, thereby regulating immune responses. Such changes may contribute to the development of silicosis by altering DC phenotype, function, and migration and by influencing the balance between Th1 and Th2 cells.